Dynamic forecasting model for indoor pollutant concentration using recurrent neural network. Issue 10 (December 2021) - Hu, Lulu; Fan, Na; Li, Jingguang; Liu, Yingwen
Accurate and reliable indoor pollutant concentration prediction is essential to solve the time-lag problem of indoor air quality control systems. Thus, the representation of time in pollutant forecasting models is very important. One approach is to introduce an Elman neural network using a direct inference strategy into the time series forecast of indoor pollutant concentration. In this study, measurements of CO2 (ppm), total volatile organic compounds (mg/m 3 ), particulate matter with a diameter smaller than 2.5 µm (PM2.5 ; µg/m 3 ), the indoor dry bulb temperature (°C) and relative humidity (%) were carried out in a classroom at a middle school in Beijing, China. To identify air pollution antecedents, input selection was conducted based on correlation analysis. The results show that the information provided by the PM2.5 time series can better simulate the dynamic relationship between input and output data (C C   = 0.963 and R 2  = 0.928). In addition to the overall goodness of fit (R 2  = 0.982) of the CO2 time series, the peak and valley prediction capability of the model was evaluated using the relative peak error ( RPE ) metric. Information from the valleys of the CO2 time series gives good results (RPE < 0.1 ). Therefore, a dynamic forecasting model with a direct inference strategy is a capable tool for identifying proper air pollution antecedents.